2018
DOI: 10.21037/atm.2018.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant therapy in acute respiratory distress syndrome

Abstract: Acute respiratory distress syndrome (ARDS) presents a complex pathophysiology characterized by pulmonary activated coagulation and reduced fibrinolysis. Despite advances in supportive care of this syndrome, morbidity and mortality remains high, leading to the need of novel therapies to combat this disease. Focus these therapies in the inhibition of ARDS development pathophysiology is essential. Beneficial effects of anticoagulants in ARDS have been proved in preclinical and clinical trials, thanks to its antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 95 publications
1
40
0
2
Order By: Relevance
“…Despite evidence about coagulation activation and impaired fibrinolysis leading to fibrin deposition in the alveolar compartment in non-COVID-19 ARDS patients [18], data about therapeutic anticoagulation's efficacy and safety is very limited in these patients [19]. Some recent investigations showed that low molecular weight heparin (LMWH) could reduce acute lung injury (ALI) in experimental models [20,21] [15].…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence about coagulation activation and impaired fibrinolysis leading to fibrin deposition in the alveolar compartment in non-COVID-19 ARDS patients [18], data about therapeutic anticoagulation's efficacy and safety is very limited in these patients [19]. Some recent investigations showed that low molecular weight heparin (LMWH) could reduce acute lung injury (ALI) in experimental models [20,21] [15].…”
Section: Discussionmentioning
confidence: 99%
“…Nebulised UFH targets pulmonary fibrin deposition and inflammation, and local administration to the lungs allows higher dosages and increases local efficacy, reduces the risk of systemic bleeding and is more effective than intravenous administration [84,85]. Importantly, previous studies have shown that following nebulisation, UFH does not enter the systemic circulation significantly which means it can be used in addition to systemic therapeutic or prophylactic anti-coagulation without concerns of furthering systemic anti-coagulation.…”
Section: Anti-coagulant Effectsmentioning
confidence: 99%
“…Adaptable nebulizer technology is ideal for combination in aerosol delivery systems where the objective is to augment lung dose by controlling, and possibly calculating and adapting to, a patient's breathing patterns. The role of nebulizers in treating respiratory disease, and symptoms of disease is the subject of numerous recent reviews, including in acute respiratory distress syndrome (ARDS) [2,3], chronic obstructive pulmonary disorder (COPD) [4,5], cystic fibrosis (CF) [6,7], ventilator-associated pneumonia (VAP) [8,9], dyspnea [10], and acute asthma [11], among others.…”
Section: Introductionmentioning
confidence: 99%